L’indemnisation des administrateurs et des dirigeants : législation, réglementation d’indemnisation, assurance - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1995)
The indemnification of corporate Directors and Officers is a complex problem. Firstly, the author describes and analyzes the provisions contained in section 124 of the Canada Business Corporations Act and in section 123.87 to 123.89 of the Quebec Companies Act. Secondly, the author questions the right of Directors to be indemnified more extensively by their corporations in situations not covered by federal and provincial legislation provided that said broader indemnity is not contrary to public order. Thirdly, he draws a parallel between the corporate by-laws on the indemnification of the Directors and Officers and the Directors' and Officers' liability insurance coverage (D & O insurance) in order to determine what can be adequately protected by corporate indemnification and whether the remainder can be covered by insurance. He concludes with the necessity for the board of directors to comply with more demanding standards of care and to develop a practical program to minimize the risks and to prevent suits against Directors and Officers.